Asuhan Keperawatan Pada Tn.R Dengan Gangguan Sistem Pencernaan: Appendisitis Post Appendiktomi Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Willi Nur Aeni; Ahmad Zakiudin; Sukirno Sukirno (Lembaga Pengembangan Kinerja Dosen, 2023)
In the digital era and now it stimulates human life in the world to adopt new patterns such as eating patterns and so on. The current era of information technology and globalization has brought many changes to people's lives, including changes in lifestyle, especially diet. Consuming excessive amounts of fast food can cause various health problems, such as obesity (overweight), diabetes (diabetes), hypertension (high blood pressure), atherosclerosis (hardening of the arteries), coronary heart disease, appendicitis (appendicitis), stroke, cancer. , and others (Amalia et al., 2022). Appendicitis is a health problem that often occurs in Indonesia. Appendicitis requires surgical intervention, because it is an acute inflammation (Rahayu et al., 2021).